2022
DOI: 10.1071/wr21113
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to conservation detection dogs: identifying motivations and understanding satisfaction in volunteer handlers

Abstract: Context The use of conservation detection dogs (CDDs) is an established, highly efficient means by which data on cryptic and low-density plant and animal species can be collected in a relatively cost-effective way. Nonetheless, the time and resource costs associated with purchasing, training, and maintaining CDDs can be prohibitive, particularly for smaller organisations seeking to contribute to environmental work. A volunteer-based model of CDD training and deployment could make highly skilled teams more ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Although the present study suggests there is clear potential for detection dogs to assist with locating P. frosti , under harsh climatic and environmental conditions, to ascertain if detection dogs are cost effective, the value of this approach will need to be compared against other survey approaches. Specifically, it would be informative to compare the efficacy of detection dogs against traditional methods (particularly human surveyors), factoring in financial costs associated with dog training, housing and welfare requirements (Rutter et al, 2022). While past studies have suggested that dogs are significantly more effective than all other methods at locating cryptic wildlife (Grimm‐Seyfarth et al, 2021), the extent of any such benefits would need to be formally quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study suggests there is clear potential for detection dogs to assist with locating P. frosti , under harsh climatic and environmental conditions, to ascertain if detection dogs are cost effective, the value of this approach will need to be compared against other survey approaches. Specifically, it would be informative to compare the efficacy of detection dogs against traditional methods (particularly human surveyors), factoring in financial costs associated with dog training, housing and welfare requirements (Rutter et al, 2022). While past studies have suggested that dogs are significantly more effective than all other methods at locating cryptic wildlife (Grimm‐Seyfarth et al, 2021), the extent of any such benefits would need to be formally quantified.…”
Section: Discussionmentioning
confidence: 99%